2019
DOI: 10.1128/msystems.00208-18
|View full text |Cite
|
Sign up to set email alerts
|

Rare Taxa Exhibit Disproportionate Cell-Level Metabolic Activity in Enriched Anaerobic Digestion Microbial Communities

Abstract: Variation in microbial activity levels is increasingly being recognized as both an important dimension in community function and a complicating factor in sequencing-based survey methods. This study extends previous reports that rare taxa may contribute disproportionately to community activity in some natural environments, showing that this may also hold in artificially maintained model communities with well-described inputs, outputs, and biochemical functions. These results demonstrate that assessment of activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 56 publications
2
22
0
Order By: Relevance
“…The disproportionally high read abundances of rRNA at low rDNA abundances for most phyla 239 ( Figure S4) confirm previous similar observations, suggesting higher activity among rare taxa 240 (Campbell, et al 2011, Jia, et al 2019, Jones and Lennon 2010, Klein, et al 2016, Wilhelm, et al 241 2014. This phenomenon could perhaps be due to under-sampling (Steven, et al 2017), but higher 242 growth rate among rare taxa could arise due to intraspecific competition or predation of abundant taxa 243 (Jousset, et al 2017).…”
supporting
confidence: 83%
See 1 more Smart Citation
“…The disproportionally high read abundances of rRNA at low rDNA abundances for most phyla 239 ( Figure S4) confirm previous similar observations, suggesting higher activity among rare taxa 240 (Campbell, et al 2011, Jia, et al 2019, Jones and Lennon 2010, Klein, et al 2016, Wilhelm, et al 241 2014. This phenomenon could perhaps be due to under-sampling (Steven, et al 2017), but higher 242 growth rate among rare taxa could arise due to intraspecific competition or predation of abundant taxa 243 (Jousset, et al 2017).…”
supporting
confidence: 83%
“…This phenomenon could perhaps be due to under-sampling (Steven, et al 2017), but higher 242 growth rate among rare taxa could arise due to intraspecific competition or predation of abundant taxa 243 (Jousset, et al 2017). In fact, by using metagenomic data, Jia, et al (2019) observed higher 244 replication rates for taxa at low relative abundances supporting that this is a real phenomenon. 245 246…”
mentioning
confidence: 89%
“…Knowing that the metabolic activities of certain microbes could be suppressed by antagonists and so may not be actively involved in a given condition (phenotype), capturing such bacteria due to their sheer presence may give a false positive association. This is supported by studies that have reported that taxonomic abundance does not correspond to transcriptional activities [ 25 , 26 , 27 ]. The library construction, assembly, and reference databases of metagenomics for annotation employ biases that are difficult to understand [ 21 ].…”
Section: Omic Techniques In Gut Microbiome Studiessupporting
confidence: 67%
“…We analyzed the sequence data according to a previously described procedure [34] using the QIIME pipeline v. 1.9.0 [35]. Briefly, after eliminating low quality reads and dereplicating, sequences were denoised and chimeras were removed with the UNOISE3 algorithm using USEARCH to form "zero-radius OTUs" (ZOTUs).…”
Section: High-throughput Sequence Analysesmentioning
confidence: 99%